2011
DOI: 10.1021/nn204156n
|View full text |Cite
|
Sign up to set email alerts
|

UV/Ozone-Oxidized Large-Scale Graphene Platform with Large Chemical Enhancement in Surface-Enhanced Raman Scattering

Abstract: We fabricated a highly oxidized large-scale graphene platform using chemical vapor deposition (CVD) and UV/ozone-based oxidation methods. This platform offers a large-scale surface-enhanced Raman scattering (SERS) substrate with large chemical enhancement in SERS and reproducible SERS signals over a centimeter-scale graphene surface. After UV-induced ozone generation, ozone molecules were reacted with graphene to produce oxygen-containing groups on graphene and induced the p-type doping of the graphene. These … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

10
320
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 355 publications
(332 citation statements)
references
References 50 publications
(85 reference statements)
10
320
2
Order By: Relevance
“…However, as it was experimentally observed originally in 2010 by Ling et al [1], the Raman intensity of phthalocyanine, rhodamine 6G, protoporphyrin IX, and crystal violet molecules all have very different enhancement factors. Furthermore, it has been shown that enhancement factors are strongly dependent on which molecule is being probed, on the laser excitation energy used, on the two-dimensional (2D) material used for the enhancement surface [8][9][10] and even on the Fermi energy of the system, as controlled by a gate voltage [6,11,12]. The dependence of the enhancement on all these parameters cannot be explained either in terms of multiple reflections, nor by the quenching of the luminescence, nor even by a combination of both.…”
Section: Introductionmentioning
confidence: 99%
“…However, as it was experimentally observed originally in 2010 by Ling et al [1], the Raman intensity of phthalocyanine, rhodamine 6G, protoporphyrin IX, and crystal violet molecules all have very different enhancement factors. Furthermore, it has been shown that enhancement factors are strongly dependent on which molecule is being probed, on the laser excitation energy used, on the two-dimensional (2D) material used for the enhancement surface [8][9][10] and even on the Fermi energy of the system, as controlled by a gate voltage [6,11,12]. The dependence of the enhancement on all these parameters cannot be explained either in terms of multiple reflections, nor by the quenching of the luminescence, nor even by a combination of both.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, various studies have dealt with the oxidation of graphene by ozone and O ions. [5][6][7][8][9][10][11][12][13][14] In an ozone generator, C atoms are removed from the graphene lattice and vacancies are formed. The morphology of exposed singlelayer and multilayer graphene samples reflects a highly disordered nature, which varies with the thickness.…”
mentioning
confidence: 99%
“…5 After ozone generation by ultraviolet light, ozone molecules react with graphene to produce O-containing groups and induce p-type doping. 8 Theoretically, it has been predicted that O atoms lined up on pristine graphene form a stable unzipped structure, in which an epoxy group breaks the lower sp 2 bond. 9,14 In addition, the fact that the energy gap can be tuned in a wide range from 0 to 4 eV demonstrates that functionalization of graphene by oxidation has serious effects on the electronic states.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…UV irradiation has been proved to be capable of either reducing or oxidizing graphene-based materials, depending on the reducing or oxidative nature of the surrounding environment. [12][13][14][15][16][17][18] We demonstrate that by simply controlling the UV etching time for dispersed GO flakes in water, the resulting GO coatings can be converted into underwater superoleophobic coatings. In addition, this method is very promising for large-scale production.…”
mentioning
confidence: 99%